PENGARUH PEMOTONGAN UMBI BIBIT DAN JENIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH - Jumini Jumini; Yenny Sufyati; Nurul Fajri (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The objective of the research was to find out a suitable bulb slicing and kind of organic fertilizer for a maximum growth and yield of onion. This research applied a randomized complete block design (RCBD), 3 by 3 with 3 replications. Factors observed were bulb slicing and kinds of organic fertilizer. Bulb slicing consisted of no cut, cut of one-third, and cut of one-fourth of onion bulbs. Organic fertilizer consisted of compost, manure of cow and manure of chicken. Variables observed were plant height, a number of onion tillers per bunch, a number of onion bulbs per bunch, wet and dry weight of bulbs per bunch. Result showed that bulb slicing significantly affected a number of onion tillers per bunch at 30 day after planting (DAP), 45 DAP, and a number of onion bulbs per bunch. However, bulb slicing did not significantly affect plant height at 15 DAP and dry weight of bulb per bunch. The best growth and yield was found at cut of one-fourth of the bulb. Organic fertilizer showed a significant effect on a number of bulbs per bunch but did not exert a significant effect on other variables. More bulbs per bunch were achieved at compost. There was no significant interaction between bulb slicing and organic fertilizer type on growth and yield of onion.